2018
DOI: 10.1039/c8cp04154g
|View full text |Cite
|
Sign up to set email alerts
|

Structural, vibrational and electronic properties of the superconductor CuxTiSe2: theoretical and experimental insights

Abstract: The crystal/electronic structure and vibrational properties of the CuxTiSe2 intercalation compounds were studied combining experimental and theoretical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…1). 6,[16][17][18][19][20][21][22][23][24][25][26][27] A ground electronic state of TiSe 2 was controversially reported in the literature. Earlier experimental electronic transport studies found that TiSe 2 is a semimetal with an overlap of electron-hole bands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). 6,[16][17][18][19][20][21][22][23][24][25][26][27] A ground electronic state of TiSe 2 was controversially reported in the literature. Earlier experimental electronic transport studies found that TiSe 2 is a semimetal with an overlap of electron-hole bands.…”
Section: Introductionmentioning
confidence: 99%
“…6,23,31,43,44 But, on the other hand, this Cu-intercalation results in a sizable expansion of the van der Waals gaps (Fig. 2a and b), 6,[22][23][24]26,27,41,[44][45][46] and, hence, could potentially reduce an overlapping of electronic bands or extend a band gap between them. These two counteracting factors suggest a possibility for Cu x TiSe 2 to be either semimetals (metals) or narrow-gap semiconductors, depending on Cu concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The high intensity feature at ∼3 eV and the weaker features between 2 eV BE and E F show T -and polarization-dependent changes. As discussed above, the ∼3 eV feature consists of Ti 3d xy,x 2 −y 2 and Ti 3d xz,yz states strongly hybridized with Se 4p states, while states from 0 to 2 eV BE have very weak contribution from Ti 3d states [44,45]. It is noted that the Ti 3d z 2 character electron band within 50 meV of E F seen in high-resolution ARPES studies [13,14,18,21,[36][37][38] at the L-point in the Brillouin zone is not observed in our angle-integrated data, as our experimental resolution is 200 meV.…”
Section: Resultsmentioning
confidence: 81%
“…Based on a cluster model analysis of XAS spectra [41], it was shown that covalency in TiX 2 (X = S, Se, Te) increases on going from TiS 2 to TiTe 2 . Further, band-structure calculations for TiSe 2 concluded significant Ti 3d xz,yz and 3d x 2 −y 2 ,xy character states in the occupied DOS at ∼3 eV BE [44,45]. This is attributed to Ti 3d-Se 4p hybridization, although Ti formally has a d 0 configuration in TiSe 2 .…”
Section: Resultsmentioning
confidence: 95%
“…The XRD 2θ values were found at 29.2, 32.9, 53.4, and 61.5° attributed to the (002), (101), (103), and (104) lattice planes of bulk 1T-TiSe 2 , respectively [JCPDS no. 71-4828]. , The other two intense peaks at XRD 2θ values of 51.9 and 63.1° are indexed to (103) and (110) lattice planes of Ti metal foil, respectively.…”
Section: Resultsmentioning
confidence: 99%